Occupational health services as an effort to increase the health of workers at PT Petrokimia Gresik during the covid-19 pandemic - Akhmad Ridhani (Nautical : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The COVID-19 pandemic has caused many changes in the corporate structure, especially in the K3 aspect, one of which is occupational health services. PT. Petrokimia seeks to provide health services to prevent or treat illness among its employees. This research method is called qualitative descriptive research. Primary data were obtained from the K3 Bureau of PT Petrokimia, as well as interviews with the SKK section. The second set of information came from Instagram, YouTube, and the PT. Petrokimia website. The results of health service research at PT Petrokimia during the COVID-19 pandemic consisted of promotive efforts, preventive efforts, provision of PPE plus medical masks for all employees, management of work nutrition and examination of the work environment, curative and rehabilitative efforts, and the provision of occupational health service facilities at PT Petrokimiagresik, which continues to pay attention to the COVID-19 health protocol and provides other facilities. The conclusion is that health services at PT. Petrokimiagresik during the COVID pandemic were still running, and the online system had been implemented and was in accordance with the Regulation of the Minister of Manpower and Transmigration No.03/MEN/1982, except for the procurement of warehouses. To control aspects of employee work nutrition, it is recommended that PT. Petrochemicals provide a canteen for its employees.